RESEARCH OF HYDRAULIC IMPACT ON THE TECHNOLOGICAL STABILITY OF SHALLOW METROTUNNEL IN DREDGING MASSIVES - Stovpnyk, S. M.; Han, A. L.; Zahoruiko, E. A.; Shaidetska, L. V. (Science and Transport Progress, 2017)
Purpose. On the basis of the results analysis of the computer simulation and laboratory studies it is necessary to determine the changes impact dependence of the hydraulic level of groundwater on the tunnels processing stability in the underground due to the deformations development of the surrounding dredging massif. Methodology. The methodological basis of the research complex consists of the analysis, generalization of known scientific results and practical experience of forecasting and preconditioning of deformations of tunnel and surrounding soil mass processing, as well as computer simulation of the critical stress-strain state of the tunnel processing at changes in the hydraulic level of groundwater. Findings. In the process of technological construction and under the non-pressure groundwaters impact, when operating tunnels of subway lines of shallow foundation, the stability of all-section machining is ensured due to the uniform hydrostatic reduction of processing. At this the sediments are within the permissible values. The results of the research show that different levels of hydrostatic pressure can occur when the groundwater level changes from both sides of the tunnel. At the same time, there is a redistribution of stresses of the soil mass around the cross section of the tunnel, which, in turn, leads to the appearance of additional non-uniform deformations and the opening of cracks in the tunnels during operation. Originality. The authors of the work firstly established the effect of changes in hydrostatic pressure, which may arise due to fluctuations in the level of groundwater on the whole-section processing of tunnels of metro lines of shallow foundation due to secondary sedimentation. The conditions of occurrence of the secondary sediment have been determined and the nature of the deformation course has been established during the operation of the shallow subway. Practical value. At the stage of designing the metro lines of the shallow foundation, it is necessary to take into account the possibility of uneven precipitation from the action of hydrostatic pressure during operation. This will avoid additional deformations during the seasonal period, reduce the number of current repairs, increase reliability and the useful life of the tunnel processing structures.